Assessing the Financial Impact of ESG Portfolio Optimization and Diversification in an Emerging Market: Evidence from Mexico - Fosado Olvera, Paula Margarita; Castillo Dieguez, Roberto Yoan (Ekonomika, 2026)
This paper evaluates the financial implications of scaling and diversifying stock portfolios based on environmental, social, and governance (ESG) criteria in the Mexican Stock Exchange. By using a sample of firms from the S&P/BMV IPC index (2020–2024), four portfolios were constructed: High ESG, Low ESG, a Benchmark, and an Optimized ESG portfolio built through quantitative algorithms. Results from GARCH (1,1) models show that High ESG portfolios exhibited higher conditional volatility, particularly during periods of uncertainty such as 2020 and 2022, while the Optimized ESG portfolio achieved faster convergence to lower risk, signaling greater stability. Random Forest analysis identified governance, leverage, and lagged WACC as the strongest predictors of financing costs, surpassing aggregate ESG scores. Backtesting further revealed that High ESG portfolios faced more frequent breaches, whereas the Optimized ESG portfolio better contained volatility but struggled with extreme losses. ESG criteria enhance the portfolio design when combined with robust financial indicators.
Keywords: ESG; portfolio optimization; GARCH model; cost of capital; Sustainable Finance; volatility; Emerging Markets